2017
DOI: 10.1111/nyas.13360
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial claudins: expression and regulation in homeostasis and inflammation

Abstract: The intestinal epithelium forms a highly dynamic and selective barrier that controls absorption of fluid and solutes while restricting pathogen access to underlying tissues. Barrier properties are achieved by intercellular junctions that include an apical tight junction (TJ) and subjacent adherens junction and desmosomes. The TJ tetraspan claudin proteins form pores between epithelial cells to control paracellular fluid and ion movement. In addition to regulation of barrier function, claudin family members con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
264
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(286 citation statements)
references
References 136 publications
9
264
1
12
Order By: Relevance
“…Additionally, its protein expression was detected throughout the crypt-villus axis of human small intestines but was only detected in undifferentiated crypt cells of human colonic tissue [36]. Other claudins follow suit regarding crypt-luminal axis expression with some pore-forming claudins (-2, -10, -13, -15) being restricted to the intestinal crypt base in murine tissue while other sealing claudins (-3, -4, -7, -8) are expressed in luminal epithelial cells [37][38][39][40].…”
Section: Tight Junction Protein Structurementioning
confidence: 99%
“…Additionally, its protein expression was detected throughout the crypt-villus axis of human small intestines but was only detected in undifferentiated crypt cells of human colonic tissue [36]. Other claudins follow suit regarding crypt-luminal axis expression with some pore-forming claudins (-2, -10, -13, -15) being restricted to the intestinal crypt base in murine tissue while other sealing claudins (-3, -4, -7, -8) are expressed in luminal epithelial cells [37][38][39][40].…”
Section: Tight Junction Protein Structurementioning
confidence: 99%
“…Thus, it was suggested that both the S-PT84 and RSLE contributed in maintaining the gut barrier integrity at the presence of LPS. Craudin-4 is dominantly expressed in the ileum and belongs as sealing Cld (Garcia-Hernandez et al 2017). It was suggested that the decrease of Cld-4 by LPS was related to the elevated intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Cld-2 is highly expressed in leaky epithelia of gastrointestinal inflammation (Luettig et al 2015). Craudin-2 forms channel for cation and water within TJs (Garcia-Hernandez et al 2017). Although Cld-2 cannot transport uncharged oligomers such as D-mannitol and LPS, increase of Cld-2 in tight junction could affect the pattern of tight junction strand, resulting in barrier disturbance (Luettig et al 2015;Liu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As circRNAs may regulate the transcription of their parent genes [32], those circRNAs described above may play roles in intestinal I/R injury The data from the mRNA microarray were also encouraging. Of the top 10 dysregulated mRNAs modulated by intestinal I/R injury, Cldn3 (claudin-3) had the highest fold change among the downregulated mRNAs and was previously identified as a key tight junction protein that helps establish the paracellular barrier of the intestinal epithelia [33]. The significantly decreased gene expression of Cldn3 and Cldn15 indicated a defect in intestinal epithelial barrier function after I/R injury [34,35], while decreased Gpx2 expression implied a low intracellular antioxidant level in intestinal I/R progression, as suggested by previous studies [36].…”
Section: Discussionmentioning
confidence: 99%